Hubungan Pengetahuan Ibu Dengan Sikap Pencegahan Penyakit ISPA Pada Anak Prasekolah di Poliklinik Anak RSUD Palabuhanratu - Astri Agustin; Ria Andriani; Kartika Tarwati (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
ISPA is a continuous cause of morbidity and death in preschool children in various countries. This research is to find out whether there is a relationship between maternal knowledge and how to prevent ARI in preschool children at the children's polyclinic at Palabuhanratu Hospital in 2023. This research was conducted to find out whether there is a relationship between maternal knowledge with attitudes towards preventing ARI in preschool children. The design in this research uses a total sampling technique, data processing and analysis using the SPSS program using the ChiSquare test with 95% confidence (0.05) with univariate and bivariate analysis. Based on the results of statistical tests using the ChiSquare test, the resulting p value was 0.000 < 0.005, which can be concluded that this research shows that there is a relationship between knowledge and attitudes towards preventing ISPA in preschool children at the Palabuhanratu Hospital children's clinic. The conclusion of this research is that there is a relationship between maternal knowledge and attitudes towards preventing ARI in preschool children and it is hoped that this will become reference material for the children's clinic at Palabuhanratu Regional Hospital to create a health education program about ARI in preschool children so that parents know how to prevent ARI.